If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -7 = -169 Reorder the terms: -7 + 5y = -169 Solving -7 + 5y = -169 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 5y = -169 + 7 Combine like terms: -7 + 7 = 0 0 + 5y = -169 + 7 5y = -169 + 7 Combine like terms: -169 + 7 = -162 5y = -162 Divide each side by '5'. y = -32.4 Simplifying y = -32.4
| 7n-93=2n-13 | | 4g-3=1g+37 | | X^2+2mx+1=0 | | 23-5n=-3(3-n) | | 17=-7+3n | | x^3-2x=5 | | 9+7=n | | 2*(3x+4)=8*(2x-4) | | (3x^2+x+1)+(2x^2-3x-5)= | | 6z-3=z+7 | | (3y+7)=4 | | 8x+3=-9x-5 | | 6x+131=3x+184 | | 0.75y+9=0.5 | | 4c^3+4c^2-24=0 | | a^2+6a-63=0 | | p(t)=-2t^2+48t+30 | | 9x-3-4x=x+8+x | | 7(2x)-(10-3x)= | | p(t)=-2t+48t+30 | | h=vt-gt | | 6x-2-2x=x+7+x | | 15(-42x-40)=15(-8x+244) | | 8x=2-x^2 | | 6(x-7)+3(x+14)+2(x-15)=-9(x-4)+3(x+7) | | 9-6x=-4x+7 | | 4.8+10m=8.53 | | -11-5r=-8(5r-3) | | 31e=102 | | 5x^2+40=30x | | -18=16 | | -11=-45r-3 |